A New Local Fractional Derivative of q−uniform Type - Valdes, Juan E. Nápoles; Medina, Jorge A. Castillo; Guzmán, Paulo M.; Lugo, Luciano Miguel (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work we present a new derivative of q-uniform type, which contains several definitions of known q-derivatives. Some examples and properties similar to those of the ordinary calculus are also presented.